Development of a 100-n hydrogen peroxide rocket engine - Krishnan, S.; Lee, Choong Won (2008)
The ongoing developmental studies on the application of hydrogen peroxide for propulsion are briefly reviewed. A detailed design-study of a laboratory scale facility of a hydrogen peroxide mono-propellant engine of 100-N thrust is presented. For the preparation of concentrated hydrogen peroxide, a distillation facility has been realized. Results of water analogy tests are presented. Initial firings using the concentrated hydrogen peroxide were not successful. Low environmental temperature, low contact area of the catalyst pack, and contamination in the hydrogen peroxide were considered to be the reasons. Addressing the first two points resulted in successful firing of the rocket engine.